Relevansi kurikulum prodi pendidikan teknik mesin FKIP Universitas Palangka Raya dengan kompetensi guru pemula SMK - I Made Supatra; Soeharto Soeharto (Jurnal Pendidikan Vokasi, 2014)
Tujuan dari penelitian ini adalah untuk mengetahui gambaran relevansi kurikulum Program Studi Pendidikan Teknik Mesin FKIP Universitas Palangka Raya dengan kompetensi guru pemula SMK, berdasarkan tinjauan terhadap profil kurikulum dan profil kompetensi mahasiswa calon guru pemula SMK. Penelitian ini merupakan penelitian deskriptif dengan menggunakan The Explanatory Sequential Design. Informasi data penelitian diperoleh dari populasi 18 orang dosen dan dari populasi 24 orang mahasiswa yang melaksanakan PPL II. Hasil penelitian menunjukkan bahwa kurikulum Program Studi Pendidikan Teknik Mesin FKIP Universitas Palangka Raya relevan dengan kompetensi guru pemula SMK dengan persentase sebesar 72,96%. Kompetensi yang dimiliki oleh mahasiswa PPL II relevan dengan kompetensi guru pemula SMK dengan persentase sebesar 63,64%. Program Studi Pendidikan Teknik Mesin FKIP Universitas Palangka Raya belum menetapkan standar kompetensi lulusan untuk konsentrasi bidang otomotif. Terdapat empat pola hubungan antara materi kurikulum Program Studi Pendidikan Teknik Mesin FKIP Universitas Palangka Raya dengan Standar Kompetensi Guru Pemula SMK. Mahasiswa PPL II belum memiliki kompetensi secara utuh sebagai calon guru pemula SMK, dan belum mampu menciptakan atsmosfer belajar yang kondusif dalam proses pembelajaran di SMK. THE RELEVANCE OF CURRICULUM OF MECHANICAL ENGINEERING EDUCATION PROGRAM OF THE FACULTY OF TEACHING AND EDUCATIONAL SCIENCES, PALANGKARAYA UNIVERSITY, WITH THE VET NOVICE TEACHERS' COMPETENCIESAbstractThe aim of this study was to determine the description of the relevance of the curriculum of Mechanical Engineering Education Program, Faculty of Teaching and Educational Sciences, Palangkaraya University, with the VET novice teachers' competencies based on the review of the curriculum profiles and the competency profiles of the VET novice teachers. This study was a descriptive study with the explanatory sequential design. This study was conducted to the curriculum of Mechanical Engineering Education Program, Faculty of Teaching and Educational Sciences, Palangkaraya University. The information of the research data was obtained from the population of 18 lecturers and the population of 24 students who performed PPL II. The results show that the curriculum of Mechanical Engineering Education Program of the Faculty of Teaching and Educational Sciences, Palangkaraya University is relevant with the VET novice teachers' competencies with the percentage of 72.96%. The competencies possessed by the PPL II students are relevant with the VET novice teachers' competencies with the percentage of 63.64%. The Mechanical Engineering Education Program, Faculty of Teaching and Educational Sciences, Palangkaraya University has not set competency standards for the concentration of automotive expertise. There are four patterns of relationship between curriculum materials of The Mechanical Engineering Education Program, Faculty of Teaching and Educational Sciences, Palangkaraya University with the VET novice teacher competency standards. The PPL II Students are not yet fully competent as VET novice teachers, and has not been able to create a conducive learning atsmosfer in the process of learning in VET.